2006
DOI: 10.1002/jcu.20190
|View full text |Cite
|
Sign up to set email alerts
|

Complete epididymal separation presenting as polyorchidism

Abstract: We describe an unusual case of a 21-month-old boy with complete separation of the testis and epididymis. Two homogeneous structures were observed in the scrotum of a newborn boy in addition to a third structure. Polyorchidism was suspected, but follow-up sonographic studies showed a decrease in the echogenicity of the left scrotal structure. Surgical exploration revealed the testis and epididymis to be completely separated, with no duplicated testis. Orchidopexy was then performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…a newborn diagnosed as polyorchidism by ultrasound during initial examination and 2 follow-up studies. Only surgical exploration, performed at 21 months after the first study, revealed the true nature of the additional oval structure [7].…”
Section: Discussionmentioning
confidence: 99%
“…a newborn diagnosed as polyorchidism by ultrasound during initial examination and 2 follow-up studies. Only surgical exploration, performed at 21 months after the first study, revealed the true nature of the additional oval structure [7].…”
Section: Discussionmentioning
confidence: 99%
“…The accessory testis has echogenic and vascular pattern identical to normal testes respectively) (Akbar et al, 2003). There are studies suggesting that imaging techniques can sometimes be unable to definitely differentiate polyorchidism from other intrascrotal pathologies (Bergholz & Wenke, 2009;Graif, Gakhal, Iacocca, & Levy, 2014;Zuppa et al, 2006). Accordingly, some authors recommend use of histologic confirmation of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the patient took the surgical treatment in hospital for the left varicocoele and the a simple scrotal exploration suffice of the scrotum was performed along the way. Furthermore, close follow-up should be performed in our patient because masses were not been completed excluded [6][7][8]. Our plan was to examine it by ultrasound and other clinical examinations every three months.…”
Section: Discussionmentioning
confidence: 99%